Comparison of Regression Analysis using Origin, Matlab, and Regression Learner App in Formulating the Linear Equation for Leg Flexibility Index - Abd Rahaman, Nur Safwah; Jumadi, Nur Anida (Evolution in Electrical and Electronic Engineering, 2021)
Silat has been practiced at every age stage and it is bringing more popularity worldwide. It focuses on a footwork technique and hand movements for self-defense and attacking the opponent. It is assumed that the greater the kicking angles of an athlete, the greater the leg flexibility index they have. Therefore, to verify this relationship, the aim of the research has been set which is to formulate the equation by using mean kicking angle and leg flexibility index based on regression analysis with the objectives to formulate the linear equation using formula y = mx + c and to evaluate the performance model based on residual plot, R-squared, MSE and RMSE. The leg flexibility index was obtained by calculated using formula of leg flexibility index by dividing the maximum range of kick with the length of leg whereas, the mean kicking angle was used from previous data collection. Both variables were used as input into OriginLab, Matlab and Regression Learner App to study the relationship by performing a straight line regression analysis as a predictive function. From that, the relationship of the graph obtained was moderate positive linear regression. The findings show that the Origin and Regression Learner App resulted the same value of linear equation which is 0.0055x+1.2705 while in Matlab is 0.0055x+1.3. It may be stated that the value in Origin and Regression Learner is more exact than in Matlab because it is calculated to 4 decimal places. The main findings show the equation from both OriginLab and Regression Learner App has recognized to be more accurate compared with Matlab as it yields a lower percent of error which has a very close to the accepted value of the leg flexibility index.